Investigating the Arctic phytoplankton variability and diversity based on modeling and satellite retrievals - Losa, Svetlana N.; Soppa, Mariana Altenburg; Oelker, Julia; Dinter, Tilman; Hellmann, Sebastian; Losch, Martin; Dutkiewicz, Stephanie; Richter, Andreas; Rozanov, Vladimir V.; Burrows, John P.; Bracher, Astrid (2017)
In our study we focus on improving our understanding of possible interactions between the open water and sea ice and the surface ocean biogeochemistry under the recently observed sea ice decline in the Arctic. In particular, the analysis of changes in phytoplankton functional types (PFTs) over 2002 to 2012 based on long-term time series of satellite retrievals and supported by a modeling study is presented. The phytoplankton dynamics as well as phytoplankton diversity in response to Arctic Amplification is simulated with the DARWIN biogeochemical model (Follows et al., 2007, Dutkiewicz et al., 2015) coupled to the Massachusetts Institute of Technology general circulation model (MITgcm) with a configuration based on a cubed‐sphere grid (Menemenlis et al. 2008). The model results are complemented with information on phytoplankton compositions retrieved with PhytoDOAS (Bracher et al. 2009, Sadeghi et al. 2012) from available hyper-spectral optical satellite measurements (SCIAMACHY and OMI), which are synergistically combined via an optimal interpolation technique with multi-spectral optical satellite data (OC-CCI).